OTIMIZAÇÃO DO PROCESSO DE TRANSESTERIFICAÇÃO EM DUAS ETAPAS PARA PRODUÇÃO DE BIODIESEL ATRAVÉS DO PLANEJAMENTO EXPERIMENTAL DOEHLERT - Carla F. C. Ruschel; Marco F. Ferrão; Francisco P. Dos Santos; Dimitrios Samios (Química Nova, 2016)
In this work, Doehlert experimental design was used to optimize the Transesterification Double Step Process (TDSP) method of methyl soybean oil biodiesel production which starts with a basic catalysis followed by an acidic catalysis. The conversion values were calculated from NMR spectra. Response surface was used to show the results of the interactions between the variables. This experimental design evaluated variables like catalyst and alcohol amount for the basic catalysis and time and temperature for the acidic catalysis. According to results obtained after Doehlert design application the alcohol amount was the main factor that influenced on the basic catalysis but for the acidic catalysis both time and temperature are important and their effects are opposite. It resulted on excellent conversions for both steps obtaining for the basic catalysis about 100% when was used like optimal conditions catalyst amount equal to 0.40 g and volume of methanol equal to 60 mL and for the acidic catalysis about 99% when was used like optimal conditions temperature of 65 °C and 90 minutes for reaction time.